Antidiabetic Effects of Foeniculum vulgare in Alloxan-induced Diabetic Male Rats (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Diabetes mellitus (DM) has become one of the most challenging health problems of the 21st century. Foeniculum vulgare (Mouri in Bengali), an ancient culinary herb, is known to reduce blood glucose levels thus reducing the risk of diabetes. This study was done to observe the antidiabetic role of Mouri in alloxan-induced diabetic male rats. Methods: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2018 to June 2019. A total of 30 healthy Wistar albino male rats, 90-120 days old, weighing between 150-180g were included in the study. After acclimatization for 14 days, they were divided into two groups: the control group (Group A) and the experimental group (Group B – diabetic rats treated with Mouri). The control group was again subdivided into Group A1 (normal control group) and Group A2 (alloxan-induced diabetic control group). Each of these groups consisted of 10 rats. All the rats received a basal diet for 21 days. In addition to the basal diet, Group A2 and Group B received a single intraperitoneal injection of alloxan 140 mg/kg on day 1 to induce diabetes. Moreover, Group B received Mouri extract 150 mg/kg/day orally for 21 consecutive days starting from day 1 of the study period. After 12 hours of fasting, blood samples were collected from the tail veins of every rat on day 1 for estimation of Fasting Blood Glucose (FBG) and serum ALT levels. On day 4 FBG levels of all the rats were measured once again. Then all the rats were sacrificed on day 22 and their blood samples were collected from the heart. The outcome variables, such as FBG level, serum levels of insulin, were measured and compared among the study groups. The pancreatic tissue was also collected and histopathology was done by standard laboratory procedure to study their histologic architecture.Result: In this study, fasting blood glucose level in diabetic rats treated with Mouri at the endpoint of the study (on day 22) was significantly lower (5.51 ± 0.47 mmol/L) than that in alloxan-induced diabetic control (13.52 ± 0.76 mmol/L) (p < 0.001) and was almost equal to that in normal control (5.38 ± 0.55 mmol/L) (p = 0.891). The serum insulin level in diabetic rats treated with Mouri (11.52 ± 0.84 mmol/L) was almost similar to that of normal control (12.46 ± 1.07 mmol/L) on day 22, whereas it was much higher than that in alloxan-induced diabetic control (8.51 ± 0.68 mmol/L) (p < 0.001). Histological study of pancreases of the rats, revealed extravasation of blood in the pancreatic acini, reduced area of islets of Langerhans with atrophy, vacuolation, degeneration, and pyknosis of β-cell nuclei and centrilobular necrosis in the alloxan-induced diabetic control rats.Conclusion: Mouri (Foeniculum vulgare) improves the glycemic status of the alloxan-induced diabetic rats.Ibrahim Card Med J 2023; 13 (1&2): 53-59